El clérigo valenciano Vicent Manuel Branchat contra Napoleón - Vicent Josep Escartí; Rafael Roca (Cahiers de Civilisation Espagnole Contemporaine)
During the invasion of Napoleon in Valencia and in the years which followed, the literature of popular nature was clearly used to mobilize the population against the French, the Frenchified and Napoleonic ideas. Vicent-Manuel Branchat, a practically unknown clergyman, was one of the writers who better illustrate this attitude: he wrote colloquia, conversations and even theatrical pieces with a clear anti-French and conservative ideology, between 1813 and 1819. Furthermore, due to popular character of the literary genres used, the choice of the Catalan language was imposed as it was reaching the masses who did not understand well the Castilian or French.